Online Media News Strategy On Vaccination Discourse: Theo Van Leeuwun’s Critical Discourse Analysis - Denni Iskandar; Wildan Wildan; Nurrahmah Nurrahmah; Muhammad Fauzi (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2023)
The vaccination discourse is one of the discourses that is always reported by the mass media because of the increasing cases of Covid-19. News about vaccinations elicited various responses from the public. This study aimed to examine the strategy of online media news related to the vaccination discourse that had resulted in various public responses. The research was conducted using Theo van Leeuwen’s theory on critical discourse analysis. Four online media consisting of KOMPAS.com, detik.com, Liputan6.com, and Tribunnews.com were chosen as data sources for this research. This study uses a qualitative method. Data in the form of phrases, clauses, and sentences were collected through reading and note-taking techniques. Then, the data were analyzed using a qualitative descriptive approach. The research results showed that the online media of KOMPAS.com, detik.com, Liputan6.com, and Tribunnews.com used exclusion and inclusion strategies in producing news discourse. However, KOMPAS.com and detik.com online media tended to use exclusion strategies that included passivation, nominalization, and substitute clauses. Furthermore, Liputan6.com and Tribunnews.com online media tended to use inclusion strategies such as nomination-categorization, nomination-identification, and differentiation-indifference. Commonly, in this vaccination discourse, the news written by these four online media were not over-criticizing the government but more emphasized driving opinions concerning various public responses to vaccination. These findings suggest readers to read information in the mass media critically. Thus, readers are not easily influenced by the conflicts that are reported